Rocky Mountain Divide : Selling and Saving the West - Wright, John B. (John Burghardt), 1950- (Book collections on Project MUSE., 1993)
The opposing forces of conservation and development have shaped and will continue to shape the natural environment and scenic beauty, of the American West. Perhaps nowhere are their opposite effects more visible than in the neighboring state of Colorado and Utah, so alike in their spectacular mountain environments, yet so different in their approaches to land conservation. Through an exploration of the cultural and historical geography of each state, this study explains why Colorado has over twenty-five land trusts, which have conserved over 42,000 acres of privately owned land, while Utah has only one trust and 110 acres conserved. John Wright traces the success of voluntary land conservation in Colorado to the state's history as a region of secular commerce. As environmental consciousness has grown in Colorado, people there have embraced the businesslike approach of land trusts as simply a new, more responsible way of conducting the real estate business. In Utah, by contrast, Wright finds that Mormon millennialism, high birth rates, and the belief that growth equals success have created a public climate opposed to the formation of land trusts. As Wright puts it, "environmentalism seems to thrive in the Centennial state within the spiritual vacuum which is filled by Mormonism in Utah." These findings reveal the underlying cultural values that cause people to conserve or develop the land they occupy. They also remind conservationists of the need to consider the strength of these values in their efforts to preserve private lands